The role of legal advisers in international law - Zidar, Andraz; Gauci, Jean-Pierre (Brill ; Nijhoff, 2016)
The Role of Legal Advisers in International Law sheds light on the position, activities and influence of legal advisers in the domain of international law. This is a novel and edifying perspective in that it surveys and appraises important undertakings of legal advisers in domestic and international legal forums and their role in the development, interpretation and application of international law. Building upon their extensive knowledge and experience, contributors to the book analyse themes such as influence of various legal traditions (including the British) on the work of legal advisers, their position in the diplomatic decision-making process, the role of ethics in providing legal advice, and their contributions - in various forms - to the development and strengthening of the international legal system. Please also see the following related titles: - British Influences on International Law, 1915-2015 - British Contributions to International Law, 1915-2015.